Agroecology Module V2.0 Documentation - Chemarin, Charlotte; Jones, Sarah; Mosnier, Aline (2024)
The agroecology module allows FABLE Calculator users to explore the effects of increasing the coverage of certain agroecological practices on cropland towards 2050. We use agroecological as an umbrella term for any practice that is distinct from intensively managed monocultures. Scenarios for the evolution of agroecological practice coverage are defined per commodity group, by country or region. The user can create scenarios that alter the coverage of one or several agroecological practices, and the rate of implementation to 2050. The module estimates the effect of a shift in the area coverage of one agricultural practice to another, using estimates from global meta-analyses. The module currently accounts for estimated effects on yield, biodiversity on cropland, soil organic carbon (SOC) stocks, and production costs through labour.